The Impact of HDPE Plastic Seeds on the Performance of Asphalt Mixtures - Daud Nawir; Achmad Zultan Mansur (Civil Engineering Journal, 2021)
Plastic waste processing is a problem that almost several countries in the Asian region are unable to overcome. One of the latest innovations carried out in the field of road pavement construction is mixing HDPE type plastic waste that has been processed into plastic seeds into the asphalt concrete mixture. Previous research has shown that HDPE plastic waste may be reused to improve the physical properties of temperature-sensitive asphalt and improve the stability of asphalt concrete. This study was conducted to determine the effect of using HDPE plastic ore as a mixed additive on the Asphalt Concrete-Wearing Course (AC-WC) using Marshall parameters. Marshall Parameters used are stability, flow, VIM, VMA, VFA, and MQ. The study was conducted in a laboratory by testing 42 samples with different levels of HDPE plastic seeds, mixed using wet methods to determine Marshall Characteristics. Manufacture of test objects using asphalt type, which has a penetration rate of 60/70. The initial research results showed that the optimal asphalt content (OAC) is 5.5%, with the percentage content of HDPE plastic seeds around 0, 1, 2, 3, 4, 5, 6, and 7% compared to asphalt weight. The results showed that the effect of HDPE plastic seed content on the AC-WC mixture increased the value of Marshall Characteristics and met all the requirements of SNI 06-2489-1991. This finding shows that HDPE plastic seeds deserve to be an alternative material for road pavements. Doi: 10.28991/cej-2021-03091744 Full Text: PDF